ENGINEERING EXCELLENCE AT SCALE: KEY METRICS FOR MEASURING CLOUD-NATIVE SOFTWARE DELIVERY - Sridhar Nelloru, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the critical role of key metrics in achieving engineering excellence at scale within cloud-native software delivery environments. It delves into the limitations of traditional metrics and introduces forward-looking indicators that provide a more comprehensive view of software delivery performance. The paper discusses the implementation of these metrics in CI/CD pipelines, emphasizing the importance of selecting appropriate metrics, integrating analytics platforms, and leveraging machine learning-based tools for monitoring and analysis. It examines how data-driven decision-making can detect bottlenecks, guide continuous improvement efforts, and correlate engineering metrics with business outcomes. The article also highlights the strategic investments that can be made based on metric insights, including justifying tooling investments, allocating resources for training, and prioritizing architectural refactoring. Furthermore, it explores the creation of feedback loops that inform technical decisions, drive cultural shifts within engineering teams, and enable adaptation to changing market demands. Finally, the paper addresses the challenges of maintaining a competitive edge, adapting to evolving technologies, and balancing innovation with stability in the pursuit of engineering excellence at scale.